Mitochondrial dysfunction in central nervous system tumors: microsatellite genomic instability and altered respiratory chian expression - Yusoff, Abdul Aziz Mohamed (Pusat Pengajian Sains Perubatan, Universiti Sains Malaysia, 2018)
Background Cancer progression involves the accurmulation of va1ous gcnetic allcr,111ons. which arc prcscnl both in the nuclear as well as 111 tho mrtochondrial Q{:•JOmes M1crcsatcllHe 1nstab1hty (MSI) is a sensitive mdic:ator of geoornic slablhty Microsalclhtes arc shon tandem repeals of sequence motifs. usually ranging tcom one to hvc DNA bases. MSI is defined by changes of mic;rosatelllte length (d..ie to e11her 1nsert10"5 or ck>letions of repefltive noncoding DNA sequences). wilhin tumor DNA compared fo that oi normal tissue. Our previous study has idenulled a r;gh pievalence of somattc mtDNA alle'al1011s in lhe mtONA D-1oop oi ml DNA In !he group 01 bra>11 tumor patients. To e•tend these findings. we analyzed fhe cccorrence o' mltcx:hondr1al m1crosaletlr.e Instability (mlMSl1 in other reglons of mtDNA m brain iumor and doterm1ned the rela!1onship belween mtMSI and mlDNA copy numbet alterations 111 ora1n tumor Method: Bran tumor tissues were collected from 45 patients along with tho corresponding blood samples. The segments ol mtDNA encompassing the cand'Clate microsatelrr.e regions were analyzed by polymerase chain reaction-High Reselufon Melt•OQ analysis (PCR-HRMA) using mtDNA·specrfic pnmers ar.d later were confirmed by direct DNA sequencing. Furthermore, the mtDNA content was analyzed by using a quantitative real time PCA method. Results: The mtMSI were onserved in 51 1% (23 out of 45) of our brain tumor pal1ents. Moreover, we found that mtDNA copy number was srgrulicamly recuc.ed 111 tumo• tissues (13.49:t9.32) compared to correspol'ldlng blood samples (36.65:t9 32). Our study also revealed that 62.2% of our patients 128 out of 45) were detected lo have the ND3 1039SA>G mL1at1on and oo specific alterations of OXPHOS complexes were observed mall analyzed brain tumors samples. Conclusion: We were able to trace lhe 1nsiabdi1y changes that occurred Jn mllochondrial genome 1n Malaysian brain tumor patients. Microsatellile mstab!lity mutation could be the 11npo11ant event in llie progression of bra.n tumor, especially 1n the association With the reduced of mtDNA COP'/ number. There-io•e, w1: propose !hat mtMSI and reduced mtDNA conlenl may play an essential role m the pathogenesis of brain tumors among Malaysian patients.